SiO₂-Based Aerogels Modified by Covalently Bonded Aromatic Acids as Potential Drug Delivery Systems - Lermontov, S.A.; Sipyagina, N.A.; Malkova, A.N.; Baranchikov, A.E.; Ivanov, V.K.; Yorov, Kh.E. (Biomedical Chemistry: Research and Methods, 2018)
Hybrid aerogels (AGs) containing NH2-group were acylated by benzoic and salicylic acids. The acylated AGs had the specific area value of 170-220m2/g and were not deacylated in H2O-iPrOH mixture at 37°С during 24h. In 0.5% HCl at 37°С hydrolysis takes place releasing free acids and giving the possibility to use aminoaerogels as drug delivery system.